PERAN COMMUNICATION TRANSPARENCY, TRUST, ATTITUDE, SUBJECTIVE NORMS DAN PERCEIVED BEHAVIORAL CONTROL TERHADAP MONEY MANAGEMENT INTENTION - Rachmad Indra Baskara; Arwini Sumardi (Program Studi Akuntansi IKOPIN, 2022)
This study aims to analyze how the influence of organization transparency on trust in organization and how the impact of trust in organization on attitude, subjective norms and perceived behavioral control and how the influence of attitude, subjective norms and perceived behavioral control on money management intention. This study uses a quantitative approach. The sample of this study is private bank employees who are exposed to information related to financial literacy from the Financial Services Authority. The data itself is collected online and offline directly to the respondents in this study. Data analysis was carried out using SEM with the AMOS program. The results showed that communication transparency has an influence on trust in the organization. In addition, trust in the organization has an influence on attitudes, subjective norms and perceived behavioral control. The results of this study also show that attitude, subjective norms and perceived behavioral control have an influence on money management intention